Implementasi Strategi Promosi dan Publikasi Digital untuk Kegiatan Rohani Gereja Katolik Keuskupan Malang - Erica Adriana; Teofilus Karnalim; I Gusti Ngurah Agung Arya Bhakta Narayana; Aland Christian; Yeremia Hari Wibowo (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
The Catholic Spiritual Revival (KRK) was a large-scale spiritual event organized by the Catholic Charismatic Renewal Body of the Diocese of Malang, aimed at revitalizing the faith and service spirit among Catholics in the post-COVID-19 period. Held on November 2, 2024, at the New Hongkong Ballroom Araya Malang, the event brought together participants from 18 different prayer communities, with a target audience of 1,200 people. To support the success of this initiative, the Publication Division—comprised of a community service team from the Faculty of Economics and Business at Ma Chung University—was tasked with planning and implementing an effective promotional strategy. The team focused on a cost-efficient and high-impact digital publicity approach, which included creating digital content for social media platforms, hosting webinars, and developing a targeted online promotion campaign. The implementation of this digital strategy proved to be highly successful. Ticket sales surpassed expectations, with over 900 tickets sold two weeks before the event and actual attendance exceeding 1,200 people. These outcomes demonstrated the strong appeal and reach of the event’s publicity efforts. In addition to increasing awareness, the visual and content strategies helped build community engagement and enthusiasm ahead of the event. This report presents a comprehensive review of the planning and execution phases of the publication strategy, highlighting key challenges, creative processes, and collaborative efforts. It also offers practical recommendations for future events of similar scale, especially in leveraging digital media to enhance participation and outreach. The success of KRK 2024 underscores the value of strategic communication and visual branding in religious and community-based events.